System design of two wheeler self-balanced vehicle - Rumi, Sheikh Mohibul Islam; Hossain, Mehdi Fakid; Islam, I.S.M. Shanamul; Rahman, Md. Khalilur (© 2014 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in the 10th France-Japan/8th Europe-Asia Congress on Mecatronics, MECATRONICS 2014; Tokyo Metropolitan UniversityTokyo; Japan; 27 November 2014 through 29 November 2014 [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/MECATRONICS.2014.7018582